2022
DOI: 10.3389/fmicb.2022.770715
|View full text |Cite
|
Sign up to set email alerts
|

Do the Reclaimed Fungal Communities Succeed Toward the Original Structure in Eco-Fragile Regions of Coal Mining Disturbances? A Case Study in North China Loess—Aeolian Sand Area

Abstract: Mining activity has caused serious environmental damage, particularly for soil ecosystems. How the soil fungal community evolves in mine reclamation and what are the succession patterns of molecular ecological networks still needs to be studied in depth. We used high-throughput sequencing to explore the changes in soil fungal communities, molecular ecological networks, and interactions with soil environmental factors in five different ages (the including control group) during 14 years of reclamation in eco-fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Moreover, Ascomycota and Basidiomycota were found to be closely related, phylogenetically. It has been reported that the species of these two phyla form symbiotic relationships with plants, which further promote the growth and development of the host plants (Ji et al 2022). Similar pattern was observed for other plants in semi-arid regions, such as perennial plants, with considerably higher abundance of Ascomycota and Basidiomycota in the soil (Na et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ascomycota and Basidiomycota were found to be closely related, phylogenetically. It has been reported that the species of these two phyla form symbiotic relationships with plants, which further promote the growth and development of the host plants (Ji et al 2022). Similar pattern was observed for other plants in semi-arid regions, such as perennial plants, with considerably higher abundance of Ascomycota and Basidiomycota in the soil (Na et al 2015).…”
Section: Discussionmentioning
confidence: 99%